Human Immunodeficiency Virus/Hepatitis C Virus Coinfection in Spain: Prevalence and Patient Characteristics. (11th March 2016) - Berenguer, Juan; Rivero, Antonio; Jarrín, Inmaculada; Núñez, María J.; Vivancos, María J.; Crespo, Manel; Téllez, María J.; Domingo, Pere; Iribarren, José A.; Artero, Arturo; Márquez, Manuel; Santos, Ignacio; et al.
Abstract : The prevalence of HCV coinfection in HIV-infected individuals in Spain has decreased significantly in the last decade. Patients with active HCV infection mainly have genotypes 1a and 4, and a high percentage have liver cirrhosis. Abstract: Background. The purpose of this study was to assess the prevalence of anti-hepatitis C virus (HCV) antibodies (Abs) and active HCV infection in human immunodeficiency virus (HIV)-infected (HIV+) patients in Spain in 2015. This was a cross-sectional study. Methods. The study was performed in 41 centers in 2015. Sample size was estimated for an accuracy of 2%, the number of patients from each hospital was determined by proportional allocation, and patients were selected using simple random sampling. Results. The reference population was 35 791 patients, and the sample size was 1867 patients. Hepatitis C virus serostatus was known in 1843 patients (98.7%). Hepatitis C virus-Abs were detected in 695 patients (37.7%), in whom the main route of HIV acquisition was injection drug use (75.4%). Of these 695 patients, 402 had HCV RNA, 170 had had a sustained viral response (SVR) after anti-HCV therapy, and 102 cleared HCV spontaneously. Hepatitis C virus-ribonucleic acid results were unknown in 21 cases. Genotype distribution (known in 367 patients) was 1a in 143 patients (39.0%), 4 in 90 (24.5%) patients, 1b in 69 (18.8%) patients, 3 in 57 (15.5%) patients, 2 in 5 (1.4%) patients, and mixed in 3 (0.8%) patients. Liver cirrhosis was present in 93 patients (23.1%) with active HCV infection and in 39 (22.9%) patients with SVR after anti-HCV therapy. Conclusions. The prevalence of HCV-Abs and active HCV infection in HIV+ patients in Spain is 37.7% and 22.1%, respectively; these figures are significantly lower than those recorded in 2002 and 2009. The predominant genotypes in patients with active HCV infection were 1a and 4. A high percentage of patients had cirrhosis. Cirrhosis is also common in patients with SVR after anti-HCV therapy.